PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA TEMA LINGKUNGAN SAHABAT KITA PADA SISWA KELAS V SDN GIRIMARGO 1 TAHUN AJARAN 2020/2021 - Isnanto Sunu Utomo; Wahyudi Wahyudi; Suhartono Suhartono (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed: (1) to describe the steps in applying Quantum Teaching, (2) to improve natural science learning outcomes through the application of the Quantum Teaching, and (3) to analyze the obstacles and solutions in applying Quantum Teaching. It was a collaborative classroom action research (CAR) conducted in three cycles. The subjects were teachers and students. Data collection techniques used observation, interviews, and tests. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results showed that: (1) the six steps to the application of Quantum Teaching were Grow, Experience, Name, Demonstrate, Repeat, Celebrate; (2) the application of Quantum Teaching improved natural science learning outcomes in theme “environment of our friends”. The increasing of student’s learning outcomes were 82.61% in the first cycle, 85.66% in the second cycle, and 86.08% in the third cycle; (3) the obstacles were: the teacher had not implemented steps: Name and celebrate, students were less confident, students did not conduct discussions, students were passive, students made some noises, learning materials were inadequate. The solutions were: the teacher applied Quantum Teaching steps appropriately, the teacher motivated the students to be more confident, the teacher guided the students in discussion, the teacher reprimanded students who made noises, the teacher prepared the learning materials before class began. It concludes that the application of Quantum Teaching improves natural science learning outcomes in theme “environment of our friends” to fifth grade students of SDN Girimargo 1 in academic year of 2020/2021.Keywords: Quantum Teaching, learning outcomes, natural science